Translanguaging Practice in Higher Education: Lecturers’ and Students’ Perspectives - Alfian Alfian (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
The notion of Translanguaging is not something new in the context of EFL classroom but, both lecturer and student may not be familiar with the basic concept and how it is implemented in the classroom, that is why this paper is presented as argumentative essay focusing to explore the basic notion of Translanguaging from the perspective of lecture and students. It tried to explain about challenges and opportunities of bringing about Translanguaging to classroom practice. From the theories and several studies discussing about the implementation of Translanguaging, it is found that several findings support the practice of Translanguaging, while others found its drawback so that it is worth investigating to see on the lecturers' and students' perspectives. Since Translanguaging changes the way people think about second language learning, it needs to be viewed by students as both a threat and an opportunity. Lecturers, on the other hand, must see it as a university-wide theme applied to Translanguaging through active and collaborative learning.